Benefício previdenciário: auxílio-reclusão (Regime Geral da Previdência Social) - Silva, José Antonio da (2010)
This work presents an analysis of basically all forms of punishment and prisons that there has been in homeland legislation, taken as a requirement for obtaining allowance benefit aid-imprisonment, whether as a result of criminal or civil illegal practices. Because it is a benefit aimed at protecting the dependents of the insurected inmate in prison in reason of that are examined with circumspection, the meaning of the utterance and the dependent relationship of dependents exhaustive and lectured about the usefulness of the existence of exceptions contained in it. Other regulatory requirements are also analyzed, as e.g., subjects, initial term, the final term suspension, termination, initial monthly rent, allowance, accumulation, effects of death, even assumed. As a scientific work, due to the academic environment at a fast pace and well combined, and the subtle questions of intellectual stimulation that living in an academic graduate stricto sensu between faculty and students, to encourage thought and provoke new thoughts and research, as well as the fruit of experience in practice of the application of Social Relations, including the sub area of Social Security Law, it contains criticism, including unconstitutionality of rules and suggestions for regulatory changes (additions and revisions), always under the pretext of improving the benefit under discussion